FRI0433 Does cardiovascular disease increase the risk of sick leave and work disability among patients with rheumatic disease?. (23rd January 2014) - van der Burg, L.; Boonen, A.; van Amelsfoort, L.; Jansen, N.; Landewé, R.; Kant, I.
Abstract : Background: Rheumatic diseases are an important cause of sick leave and work disability in almost all Western societies.[1, 2] Up until now, the majority of studies has been performed in the inflammatory rheumatic diseases (e.g. rheumatoid arthritis) while less evidence is available for other rheumatic diseases that are more prevalent and potentially have a greater burden on society (e.g. osteoarthritis (OA)). Further, although the risk for cardiovascular comorbidities in rheumatic disease receives much attention, it has never been studied to what extent these cardiovascular co-morbidities predispose for higher levels of sick leave or work disability in employed individuals with rheumatic disease. Objectives: To determine the excess risks of sick leave and work disability due to rheumatic diseases in employees and to explore their interaction with cardiovascular co-morbidities. Methods: Employees (n=12, 140) from 45 companies in the Netherlands were followed for 10 years (1998-2008). Questionnaires were used to assess employment status and self-reported disease. In 50% of the cohort members self-reported rheumatic and cardiovascular diseases was verified and specified with hospital records. Company records provided individual sick leave data for the first two-and-a-half years of follow-up. Poisson regressions and Cox proportional hazard models were applied to determine the impact of self-reported and verified diseases on sick leave and work disability respectively, with adjustment for potential confounders. Interactions between rheumatic diseases and cardiovascular disease were tested. Results: Sick leave was significantly (p<0.001) increased for cohort members with self-reported rheumatic disease and cardiovascular disease, respectively, as compared to cohort members without those diseases. Cardiovascular co-morbidity did not convey for higher sick leave in participants having rheumatic disease (p>0.05). The risk of becoming work disabled over ten years was significantly increased for self-reported rheumatic diseases (HR 6.76, 95%>CI: 3.86 to 11.86) and cardiovascular diseases (HR 4.19, 95%>CI: 2.31 to 7.59), as compared to cohort members with those diseases. In those with a self-reported rheumatic disease, co-occurrence or development of cardiovascular co-morbidity did not further contribute to sick leave or work disability. In the sample verified by clinical review, sick leave was more increased for OA (p<0.05) and cardiovascular disease (p<0.001) while work disability occurred especially frequent in OA (HR 12.4, 95%>CI: 1.6 to 13.7) and fibromyalgia (HR 14.2, 95%>CI: 2.0 to 16.5), as compared to cohort members with those diseases. Conclusions: Self-reported and verified rheumatic or cardiovascular diseases among employed individuals are associated with a higher risk of sick leave and work disability, but show no additive or synergistic effects on these domains when both are present. References: Gobelet C, Luthi F, Al-Khodairy AT, Chamberlain MA. Work in inflammatory and degenerative joint diseases. Disabil Rehabil. 2007 Sep 15;29(17):1331-9. Woolf AD, Pfleger B. Burden of major musculoskeletal conditions. Bull World Health Organ. 2003;81(9):646-56. Disclosure of Interest: None Declared